Utilização de serviços odontológicos, autopercepção da necessidade de tratamento e da condição de saúde bucal dos idosos brasileiros, 2002/2003: Projeto SB Brasil - Andrea Maria Eleuterio de Barros Lima Martins (2008)
Introduction: Studies aimed at understanding the aging process and their consequences are necessary due to an observed growth in population ageing in the last few decades. In dentistry, oral health self-perception might influence and be influenced by the behavior ofindividuals, i.e., the use of dental care services might be both a consequence of the individuals self-perceived oral health and awareness of need for dental care as well as the use of dental care might influence self rated oral health. So, the triad use of dental care services,self-perception of oral health and awareness of need for dental care is complex and inseparable. Objectives: The aim here is to investigate, among the Brazilian elderly, factors associated with the use of dental care services, awareness of need for dental care and negative self-perception of oral health, in an attempt to better understand the inter-relations among such variables. Method: The data used consist of a sample from a nationwide household survey on oral health among the elderly, conducted by the Brazilian Ministry of Health in 2002/2003 (SB Brasil Project). This thesis comprises three articles, each dedicated to one ofthe three main objectives mentioned above. Factors related to the use of dental care services were investigated using Andersen & Davidsons theoretical model (1997), which takes into account demographic characteristics, variables concerning resource availability as well aspredisposition. Due to specificities of oral health in the investigated sample, the analyses were carried out in two separate sets, dentate and edentate ones, using multiple logistic regression. Individuals within each set who made use of dental services in a given year were comparedwith those who had made use of dental care services more than one year before that. Regarding those factors related to awareness of need for dental care, Gift, Atchison & Drurys 1998 Model was used in the analysis which allowed a comparison between individuals who were or were not aware of need for dental care. The analysis used robust Poisson regression. Factors associated to a negative oral health self-perception were investigated among 5014 elderly individuals who answered a question on oral health self-perception. As in the former analysis, an expanded version of Gift, Atchison & Drurys 1998 Model was also used along with robust Poisson regression. Results: Of 5009 participants who had made use of dental services at least once, 46% were dentate and 54% edentate. Prevalence of use of dental services in the preceding year in both groups was 27 and 10%, respectively. Among dentate participants, the rate of use was higher among those with more years of schooling, those who perceived their chewing as poor/very poor and among those who reported feeling oral pain; rate of use was lower among those who did not have information on oral health, those whoperceived their oral health as poor/very poor, those with lower per capita income, those who required prostheses and used them as well as those who required prostheses but did not use them, those with periodontal problems and among those with a higher number of extracted teeth. Among edentate participants, the utilization rate was higher among those with more years of schooling and those reporting oral pain; and lower among non-whites and those who did not have information concerning oral health. Regarding the self-perceived need for dental care, 2928 (55%) said they needed oral treatment. The proportion who perceived the need for dental care was lower among those who were 70 years or more, who had not received information on how to avoid oral problems and among edentulous. Self-perceived need for dental care was greater among those who rated their oral health as regular or bad, theirappearance as regular or bad, and their chewing as regular or bad. Self-perceived need was also greater among those who reported toothache or gum pain in the last six months and those who needed dentures in one or two arches. Regarding oral health self -perception, 870 (17.4%) said they had self- rated their oral health as regular or bad. Compared with those with 10 or more teeth, the prevalence of a worse self-rated health was significantly lower among the elderly with 1-9 teeth and among edentulous. Conversely, it was greater among brown,black and Indian subjects, among those who never used dental care, those who have oral mucosal lesion, who reported toothache or gum pain in the last six months, who perceived their appearance and their chewing as regular or bad, who perceived their social relationsaffected for oral conditions and among those who perceived a need for dental care. Conclusion: The oral health of the elderly in Brazil is deficient and the use of dental services was lower among those who needed it most. Different factors are associated with the use of dental services for dentate and edentate individuals. Only those factors related to schooling,access to information on oral health and occurrence of toothache and gum pain in the previous 6 months are similar for both groups. Access to information along with some oral heath condition and subjective questions identified in this study were associated with self-perceivedneed for oral treatment. These results also reinforce the importance of enabling people to identify early non-painful symptoms and signs of oral mucosal lesion, of caries and periodontal disease in order to better assess their need of dental care. On the other hand, the analysis of the self-perceived oral health status shows that subjective conditions were more strongly associated with oral health perception than with objective ones. The association between the use of dental care services with oral health self-perception suggests that a regular use of dental care services might possibly keep the elderly informed and with a better knowledge about their own treatment needs, thus influencing their behavior and their life quality. Public investment in oral health is required to minimize the inequities and change this scenario. The availability of dental services and considerations about the elderly perceptions of their oral heath conditions might help improve their life quality. uso, serviços, odontológicos, idosos, necessidade, tratamento, autopercepção, saúde bucal.